Mortality in Barrett's oesophagus: results from a population based study. Issue 8 (15th July 2003) - Anderson, L A; Murray, L J; Murphy, S J; Fitzpatrick, D A; Johnston, B T; Watson, R G P; McCarron, P; Gavin, A T
Abstract : Background: Patients with Barrett's oesophagus have an increased risk of oesophageal adenocarcinoma but this cancer only accounts for a small proportion of deaths in these patients. Other causes of death are reportedly raised in this group. We examined cause specific mortality among individuals in a population based Barrett's oesophagus register. Methods: We constructed a register of all patients diagnosed with columnar mucosa (including specialised intestinal metaplasia) of the oesophagus within Northern Ireland between 1993 and 1999. Deaths occurring within this cohort until 31 December 2000 were identified and mortality rates were compared with the general population. Results: Overall mortality was not raised in Barrett's patients. During 7413 person years of follow up in 2373 patients there were 253 deaths (standardised mortality ratio (SMR) 96 (95% confidence interval (CI) 84–107)). Mortality from oesophageal cancer was raised in patients with specialised intestinal metaplasia (SMR 774 (95% CI 317–1231)) but only 4.7% of patients died from this cancer. Mortality from stroke (SMR 65 (95% CI 37–93)) was significantly lower than the general population while mortality from non-cancerous digestive system diseases was significantly higher (SMR 211 (95% CI 111–311)). Mortality rates from all other causes were similar to those of the general population. Conclusions: This study demonstrates that the overall mortality rate in patients with Barrett's oesophagus is closely similar to that of the general population. Oesophageal cancer mortality was raised but is an uncommon cause of death in these patients who also appear to have a reduced risk of death from stroke.